A New Surgical Protocol For Horizontal Ridge Augmentation: Simplified Apposition Technique. Human Histologic and Radiographic Analysis After 2.5 Years of Follow-Up, A Case Report - Grassi, Andrea; Memè, Lucia; Orsini, Giovanna; Licini, Caterina; Orilisi, Giulia; Bambini, Fabrizio (Archives of Clinical and Medical Case Reports, 2020)
Following tooth extraction, alveolar ridge undergoes a physiological and inevitable remodeling process that could influence the prosthodontic rehabilitation. Therefore, augmentation of an insufficient bone volume is often indicated, although it remains a significant challenge in clinical practice. The aim of this case report was to scientifically validate a new minimally invasive surgery technique called “Simplified Apposition Technique” (S.A.T), which consists in the use of deproteinized bovine bone, human fibrin glue and collagen membrane in association with a post-extraction socket, in order to obtain an increase of the horizontal ridge dimension in the nearby atrophic bone crest. A 69-years-old man patient was enrolled in this study. The hopeless tooth 4.7 was extracted and the ridge reconstruction and the socket preservation were carried out following S.A.T. After 11 months, the formation of newly bone was evaluated through radiographic analysis (Cone Beam Computed Tomography, CBCT) comparing the status before and after surgery and at 2.5 years of follow-up. Simultaneously, an implant was placed in the regenerated site and the bone chips remaining in the drills were used for the histological evaluation. The CBCT revealed an increase of the bone crest width from 3.7 to 6.5 mm and, after 2.5 years of follow-up, the bone width has remained stable. The histological evaluation showed various stages of bone formation and maturation with a good integration of the regenerated area. According to these results, S.A.T can be considered a good surgical technique for horizontal ridge augmentation in the atrophic bone, near the extraction site.